PENINGKATAN PEMAHAMAN MASYARAKAT KAMPUNG WISATA TEMATIK MASYARAKAT RT 01 DAN RT 02 KELURAHAN PANUNGGANGAN UTARA - Marchelia Gupita Sari; Imaniar Sofia Asharhani; Anisza Ratnasari (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
The Thematic Tourism Village Program in Tangerang City seems to have been asked by the city government as an effort to improve people's welfare. The active role of the community is very much needed in the development of the environment in which they live. Likewise in determining the content or theme in planning the Thematic Tourism Village so that it is right on target. The community is expected to be the subject of development, not only as recipients of policies because they have an impact on their daily lives. On the one hand, the potential of society and nature, both tangible and intangible, and the aspirations of the community should be explored as the basis for determining the theme. Pradita University as a university within the scope of the Banten province scale assists the people of North Panunggangan Village as a form of implementing Tridarma. In the planning steps of the Thematic Tourism Village by the Tangerang City Government, the steps for finding ideas are data collection or documentation, mapping, and socialization of Thematic Tourism Villages. Increasing this understanding is an important first step considering that no similar activity has been found at the locus of activity, even though the community needs it so that the development of Thematic Villages is more focused. The results of the pre-test and post-test showed that there was an increase in understanding after the socialization was carried out. The discussion was well established as evidenced by the residents' answers to questions about their opinions on the desire and awareness of the potential of the area to be developed into a tourist village.